2018
DOI: 10.1111/bph.14537
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protective effect of neferine through the modulation of nuclear factor erythroid 2‐related factor 2 signalling in ischaemic stroke

Abstract: Background and Purpose Ischaemic stroke is a leading cause of death and long‐term disability. Promising neuroprotective compounds are urgently needed to overcome clinical therapeutic limitations. Neuroprotective agents are limited to single‐target agents, which further limit their clinical effectiveness. Due to the brain's particular energy requirements, the energy micro‐environment, centred in mitochondria, is a new research hotspot in the complex pathology of ischaemic stroke. Here, we studied the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 60 publications
3
30
0
Order By: Relevance
“…In addition, luteolin has been found to enhance autophagy in studies of other diseases (Xu et al, 2014;Hu et al, 2016;Cao et al, 2017). Additionally, the administration of autophagic inhibitors such as CQ, has been shown to be associated with exacerbating disease progression (Yang et al, 2018a;Wu et al, 2019). These findings are consistent with our present results, such that we found that luteolin enhanced autophagy and activated the p62/Keap1/Nrf2 pathway, and this effect was reversed by the autophagic inhibitor, CQ, in our ICH model ( Figure 7).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, luteolin has been found to enhance autophagy in studies of other diseases (Xu et al, 2014;Hu et al, 2016;Cao et al, 2017). Additionally, the administration of autophagic inhibitors such as CQ, has been shown to be associated with exacerbating disease progression (Yang et al, 2018a;Wu et al, 2019). These findings are consistent with our present results, such that we found that luteolin enhanced autophagy and activated the p62/Keap1/Nrf2 pathway, and this effect was reversed by the autophagic inhibitor, CQ, in our ICH model ( Figure 7).…”
Section: Discussionsupporting
confidence: 91%
“…The results of related studies have indicated that by physically isolating Keap1 and impairing the ubiquitylation of Nrf2, p62 mediates the activation of Nrf2 and its downstream pathways and plays an important role in antioxidative processes (Jiang et al, 2015). In the process of exploring new drugs, up-regulation of autophagy has been found in numerous disease-model studies (Yang et al, 2018a;Rusmini and Cortese, 2019) and activation of the p62/Keap1/Nrf2 pathway has been shown to play a role in alleviating systemic diseases (Sun et al, 2016;Su et al, 2018) and in ameliorating brain injury, such as ischemic stroke (Wu et al, 2019). Our present findings were similar to those described above.…”
Section: Discussionmentioning
confidence: 99%
“…Neferine has been reported as antioxidant [ 17 ], anti-tumor [ 18 ], anticancer [ 19 ], antidepressant [ 20 ], autophagy inducer [ 21 ], anti-inflammation [ 22 ] and, anti-diabetic [ 23 ]. The study shows that NF is an activator of nuclear factor erythroid 2-related factor 2 (Nrf2) activator [ 24 ] which can reduce oxidative stress. Sulforaphane, a naturally occurring isothiocyanate produced by cruciferous vegetables such as broccoli, is a potent Nrf2 activator and potentially used as anti-cancer therapy [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Nef induced also autophagy and an association between Nrf2 and autophagy was suggested. In particular, the pathway p62/Keap1/Nrf2 seemed to have a role in Nrf2 activation [ 126 ].…”
Section: Natural Compounds As Modulator Of Nrf2 Pathway In Stroke mentioning
confidence: 99%